Progressive Muscle Relaxation, Classical Music Therapy To Reduce Stress Of End Students : Relaksasi Otot Progresif, Terapi Musik Klasik Terhadap Penurunan Stres Mahasiswa Tingkat Akhir - Lengsi, Viona Tri; Mizawati, Afrina; Kurniawati, Ps. (Jurnal Kebidanan Midwiferia, 2021)
Prolonged and unresolved stress conditions can affect the hemeostasis of the human body system which will cause physical and psychological disorders. This study aims to determine the differences in the effectiveness of progressive muscle relaxation and classical music therapy to reduce stress in the final year students at the Polytechnic Ministry of Health Bengkulu in 2020. The study used a Quasi Experiment design with a two-group pretest-posttest design conducted at the Polytechnic of the Ministry of Health Bengkulu. The sampling technique uses non-probability sampling with the type of purposive sampling with a total sample of final year students as many as 60 people divided into 2 intervention groups. Data were analyzed using univariate analysis, bivariate using the Wilcoxon Signed Rank and Mann Whitney test. Wilcoxon Signed Rank test results show that there is an effect of progressive muscle relaxation on stress reduction (p-value = 0,000), there is an effect of classical music therapy on stress reduction (p-value = 0,000). Mann Whitney test results p-value 0.004 <0.05 which means there is a significant difference in effectiveness between progressive muscle relaxation interventions with classical music therapy interventions in reducing stress, where progressive muscle relaxation interventions are more effective. The results of this study are expected to be a source of information and solutions that can help final year students reduce stress levels by using progressive muscle relaxation methods that can be done anywhere and anytime. So it easily controls the stressor that causes stress levels for students.